Desafios e perspectivas da governança em segurança pública: uma avaliação do pacto por um Ceará pacífico no território do Vicente Pinzón - Ferreira Filho, Cristovam Colombo Cirqueira (2019)
The present research focused on the actions of the "Pact for a Ceará Pacific", an innovative proposal that sought to implement a new intervention of public security policy in the state of Ceará, whose intersectoriality aims at reducing violence and crime, taking as a cut the proposal the limits of the governance guidelines and what this meant for the success and goals of the Program. It was evaluated to what extent the governance actions developed from the Integrated Security Unit (UNISEG), a model structure proposed by the public security policy located in the territory of the Vicente Pinzón neighborhood, in the city of Fortaleza / CE, were being executed in order to describe and to understand governance strategies from the perspective of preventing and reducing Violent Lethal and Intentional Crimes - CVLI between 2016 and 2017. Methodologically, a Dense Impact Assessment was adopted with qualitative and quantitative analyzes. Ceará Pacífico has adopted a multi-sectoral line of action with public bodies and entities at the local, regional and national levels in partnership with civil society. The Program took place through interdisciplinary activities, articulating the areas of Public Security and Social Defense, Justice and Citizenship, Human Rights, Education, Science and Technology, Health, Policy on Drugs, Culture, Sport, Urban Development and the Environment, and Youth Faced with the present conjuncture of affirmative public security policies, the question was: what are the structural characteristics that the government has proposed for the prevention and reduction of percentages of CVLI? Two hypotheses have been raised. The first is to assume that there was a positive relationship with the policy model being implemented and its ability to change the rates of violence in the Vicente Pinzón neighborhood. The second is that there was a negative relationship in managing a crisis in public security in an integrated and multisectorized way from the perspective of an interinstitutional culture cooperated / integrated in Ceará Pacific. The study took into account the bases, principles and guidelines advocated by the Ceará Pacific Program in relation to its governance, seeking a counterpoint with criminal rates at the time of the research. It was based on the assumption that public security should be treated as a social issue where it would be fundamental to reconstruct the role of Civil and Military Police in the present, within a new way of pondering and fulfilling its constitutional role, making possible the optimization of police cadres and the implementation of new strategies and methods for fostering social peace and public order based on human rights and citizenship, since crime is something that divides society and if it divides, it accentuates social inequalities. Violence does not fulfill the full meaning of living in the territory of Vicente Pinzón, because there is a place of solidarity of cooperation of joys and parties, so it is suggested that the public security policy does not look at that place as a singular space only by violence.